2003
DOI: 10.1002/cncr.11647
|View full text |Cite
|
Sign up to set email alerts
|

Extraocular retinoblastoma: A 13‐year experience

Abstract: The rheological behavior of PBT/LLDPE and PBT/LLDPE‐g‐AA blends [where PBT is poly(butylene terephthalate), LLDPE is linear low‐density polyethylene, and AA is acrylic acid] under a capillary flow was investigated with a capillary rheometer. The Utracki equation was used to describe the viscosity–composition dependence of PBT/LLDPE and PBT/LLDPE‐g‐AA blends at low shear stresses. However, at high shear stresses, this equation was not suitable for these blending systems. There existed a maximum on the curves of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
98
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(103 citation statements)
references
References 47 publications
3
98
0
2
Order By: Relevance
“…A subsequent study showed that 12 patients with positive optic nerve surgical margins were all event-free survivors following chemotherapy as above and orbital radiation therapy of 4,000 -4,500 cGy. A similar successful study was reported from Brazil [80].Patients with metastatic extraocular disease have a poor prognosis when treated with regimens of conventional doses of chemotherapy. There are several reports now suggesting that high-dose chemotherapy with stem cell rescue combined with EBR for areas of bulky disease at diagnosis is beneficial, with some long-term survivors among patients with metastatic disease not involving the central nervous system (CNS) [81][82][83][84][85].…”
supporting
confidence: 67%
“…A subsequent study showed that 12 patients with positive optic nerve surgical margins were all event-free survivors following chemotherapy as above and orbital radiation therapy of 4,000 -4,500 cGy. A similar successful study was reported from Brazil [80].Patients with metastatic extraocular disease have a poor prognosis when treated with regimens of conventional doses of chemotherapy. There are several reports now suggesting that high-dose chemotherapy with stem cell rescue combined with EBR for areas of bulky disease at diagnosis is beneficial, with some long-term survivors among patients with metastatic disease not involving the central nervous system (CNS) [81][82][83][84][85].…”
supporting
confidence: 67%
“…Such cases are more frequent in developing countries, occurring in more than 50% of children in some MICs compared to developed countries where they usually occur in less than 20% of the enucleated eyes. Studies in many upper MICs have yielded encouraging results, with survival rates greater than 80% for patients with these conditions [23,45,46]. However, as opposed to other childhood malignancies, there are no randomized studies to support the treatment decisions in these cases.…”
Section: Treating Patients With High-risk Pathology Featuresmentioning
confidence: 99%
“…5 In one study of chemotherapy, the patients had extraocular retinoblastoma. 130 The remaining studies were of patients with intraocular retinoblastoma or the type of retinoblastoma was not explicitly stated. Three studies explicitly stated that the participants had newly diagnosed retinoblastoma 130,131,133 and one study explicitly stated previous treatments that had been received.…”
Section: Participantsmentioning
confidence: 99%
“…130 The remaining studies were of patients with intraocular retinoblastoma or the type of retinoblastoma was not explicitly stated. Three studies explicitly stated that the participants had newly diagnosed retinoblastoma 130,131,133 and one study explicitly stated previous treatments that had been received. 38 However, the remaining studies were unclear as to whether patients had received previous treatments, although some specific previous treatments were excluded in individual studies.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation